A case report on ofloxacin-induced Stevens–Johnson syndrome: Scorten-based approach - T, Afina; Fasil, C Mohammed; Rajendran, Kannan; Marecar, Masthan; Ravichandran, Ashwath; Joan, MC Merlin; Ravichandran, Shivapriya (Indian Journal of Case Reports, 2024)
Stevens–Johnson syndrome (SJS) is a rare immune-mediated severe cutaneous adverse reaction with an incidence rate of 0.05–2 persons/ million population/month. Drugs are the most commonly implicated in 95% of cases. In our report, a 52-year-old male patient presented with chief complaints of skin rashes over the body and was having a history of using a tab. ofloxacin for gastroenteritis. The severity of SJS was assessed using SCORTEN (=1). The drug can be considered as a probable/likely cause of adverse drug reaction as per causality assessment of the suspected adverse drug reactions. Early diagnosis helps the clinician to elude secondary infection and subsequent complications. It highlights the mandatory reporting of the offending drug and the necessity of pharmacovigilance in different countries.